A method to estimate the energy production of photovoltaic trackers under shading conditions. (15th October 2017) - Díaz-Dorado, Eloy; Cidrás, José; Carrillo, Camilo
Graphical abstract: Highlights: A method for analysis of PV tracker parks under mutual shading conditions is presented. The size and geometry of the shadowed area between trackers is analyzed. Energy is estimated by means of a detailed electrical model for the entire PV-tracker. Impact of planning parameters, like layout or PV configuration, on energy is analyzed. Abstract: Energy produced by a photovoltaic park mainly depends on solar irradiance. However in order to estimate the energy production, it must be taken into account the technology of PV-modules, their layout and the electrical connection between them. Furthermore, the energy losses, especially those related to non-uniform distribution of irradiance must be considered. In this context, in a PV-park it is specially important losses related to shadows between trackers. These must be properly estimated to propose different configurations or to evaluate the efficiency of the installation. In this context, this article presents a methodology to evaluate the energy production of a PV-park where PV-trackers are modeled from their simplest elements to the PV-array. The energy calculation includes losses; therefore, shadows are analyzed and included as irregular distributions of irradiance along the tracker plane. The presented method allows for the analysis of different design criteria: PV-cells and PV-modules arrangement, PV-cell electrical connections inside a module and electrical connections between PV-modules, tracker layout on the ground and tracker dimensions. Furthermore, the proposed method allows evaluation of the annual energy generation and the losses due to the trackers' shadows, accounting for the irradiance and the temperature.